PAI INDEPENDENT CURRICULUM ASSESSMENT CONCEPT IN SCHOOLS OR MADRASAH - Wanojaleni, Kartika (Proceeding of International Conference of Islamic Education, 2023)
The purpose of this study was to determine the concept of independent PAI curriculum assessment in schools or madrasas. This study uses a literature approach by collecting references from journals and regulations related to independent curriculum assessment. The results of this study are assessments in the independent curriculum including: diagnostic assessments, namely assessments before learning, formative assessments, namely assessments during the leraning process and summative assessments, namely assessments at the end of the learning process. The form of the assessment consists of: first, the attitude of the Pancasila students profile and the profile of the rahmatan lili’alamin student can be in the form of observation, self-assessment, peer assessment, and anecdotal. Second, performance consisting of presentations, plays, exhibitions of work, journals. Third, the written test consists of: multiple choice, essay, filling, short answer, true-false. After carrying out the diagnostic assessment, formative assessment and summative assessment carry out enrichment and remedial enrichment, namely learning activities given to students with high achievements so that they can develop their potential optimally. While remedial is given to students who need guidance to understand the material or repeat learning.